The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.psym.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HIV Testing in Inpatient Psychiatry

Abstract: Three interventions of varying intensity were associated with a 5-fold increase in HIV testing on an acute inpatient psychiatry service. Nonetheless, 70% of inpatients were not tested. Continued efforts are needed to increase HIV testing in inpatient psychiatric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Following title and abstract screening, 25 full-text articles were screened for potential inclusion (the remaining articles were primarily excluded due to no use of a clinical champion, or no use of intervention in drug and alcohol or mental health). Eight articles were excluded after full text screening due to insufficient information about clinical champions ( Chang et al, 2013 ; Cohen et al, 2013 ; Kathol et al, 2010 ; Sunderji et al., 2019 ), and use of an intervention not focused on drug and alcohol or mental health treatment ( Banks et al, 2014 ; Bentz et al, 2007 ; Haynes et al, 2011 ; Shumway et al., 2018 ) or in a mental health or drug and alcohol treatment setting ( Ballard et al, 2018 ; Leathers et al., 2016 ; McCabe et al, 2013 ). Two selected studies reported on the same trial ( Hagedorn et al, 2019 ; Harris et al, 2017 ) whereby the Hagedorn et al study is presented here given that it reported on clinical champions although some information was extracted from Harris et al Thirteen (13) articles were included in the final synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Following title and abstract screening, 25 full-text articles were screened for potential inclusion (the remaining articles were primarily excluded due to no use of a clinical champion, or no use of intervention in drug and alcohol or mental health). Eight articles were excluded after full text screening due to insufficient information about clinical champions ( Chang et al, 2013 ; Cohen et al, 2013 ; Kathol et al, 2010 ; Sunderji et al., 2019 ), and use of an intervention not focused on drug and alcohol or mental health treatment ( Banks et al, 2014 ; Bentz et al, 2007 ; Haynes et al, 2011 ; Shumway et al., 2018 ) or in a mental health or drug and alcohol treatment setting ( Ballard et al, 2018 ; Leathers et al., 2016 ; McCabe et al, 2013 ). Two selected studies reported on the same trial ( Hagedorn et al, 2019 ; Harris et al, 2017 ) whereby the Hagedorn et al study is presented here given that it reported on clinical champions although some information was extracted from Harris et al Thirteen (13) articles were included in the final synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Involuntary patients are frequently unwilling to participate in treatment, and admissions often end abruptly when patients are released against medical advice. 22 As a result, it is frequently challenging to discharge involuntarily admitted patients on a recommended ART regimen. It may be that outpatient primary care is better suited to prescribe ART for many PLWH and people with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys over the past 2 decades (5-7) found low rates of risk behavior assessment and HIV testing-and of referrals for both-in outpatient mental health settings in New York. Rates of HIV testing in this population are just under 7% (8).…”
mentioning
confidence: 96%